Sociality in African mole-rats : exploring how rainfall affects dispersal and genetic exchange in the Natal mole-rat (Cryptomys hottentotus natalensis) - Bennett, Nigel Charles (University of Pretoria, 2023)
Thesis (PhD (Zoology))--University of Pretoria, 2022.